The Development of Course Selection Guidance System - Zaidi, Nur Hilda; Abdul Hamid, Norhamreeza (Applied Information Technology And Computer Science, 2023)
Choosing a career pathway after completing the Sijil Pelajaran Malaysia (SPM) examination is a significant challenge for students. To address this challenge, course selection counselling sessions with school counsellor are one of the best initiatives to expose students to a variety of potential pathways. However, the current approach used in these sessions is inefficient. In response, the Course Selection Guidance System (CSGS) has been developed as a supporting tool to enhance the traditional counselling process. Prototyping model is implemented because it enables an iterative development approach and allows for flexibility in requirement changes. CSGS aims to assist Form 5 students in identifying suitable diploma courses. By answering assessment, students will receive diploma course recommendations from two universities which are Universiti Tun Hussein Onn Malaysia (UTHM) and Universiti Putra Malaysia (UPM) that aligned with their interests and qualifications. The CSGS is intending to streamline counselling sessions and reduce manual research time.